Dynamic response and reliability analysis of tall buildings subject to wind loading - Zhang, Lin-lin; Li, Jie; Peng, Yongbo (Journal of wind engineering and industrial aerodynamics, 2008)
This paper explores the wind stochastic field from a new viewpoint of stochastic Fourier spectrum (SFS). The basic random parameters of the wind stochastic field, the roughness length z 0 and the mean wind velocity at 10 m height U 10, as well as their probability density functions (PDF), are obtained. It provides opportunities to use probability density evolution method (PDEM), which had been proved to be of high accuracy and efficiency, in computing the dynamic response and reliability of tall buildings subject to the wind loading. Principals and corresponding numerical solving algorithm of the PDEM are first presented. Then, the adopted model of the wind stochastic field is described briefly. The simulation method of the fluctuating wind velocity based on the SFS is introduced. Finally, as an example of the application of the PDEM, a 20-storey frame subject to wind loading is investigated in detail. The responses, including the mean value and the standard deviation, and the reliabilities of the frame are evaluated by the PDEM. The results demonstrate that the PDEM is applicable and efficient in the dynamic response and reliability analysis of wind-excited tall building.